Correlating assessment between clinical features and morphologies on CT scan of mandibular condyle fracture - Nguyen, Van Minh; Hoang, Vu Minh; Vo, Khac Trang; Le, Trung Thong (Tạp chí Y Dược Huế, 2023)
Background: Among mandibular fractures, condyle fractures are common injuries which directly affect the occlusal function and aesthetics of the patients. Accurate diagnosis based on clinical and radiographic features helps to choose the appropriate treatment. This study aims to evaluate clinical features, morphologies on CT Scan of mandibular condyle fractures and analyze the relationship between these characteristics. Materials and methods: A cross-sectional study on 30 patients with mandibular condyle fractures were conducted at Department of ENT - Ophthalmology - Odonto Stomatology in the Hospital of Hue University of Medicine and Pharmacy, from December 2021 to June 2023. Results: The male:female ratio was about 2:1, the main cause of fractures was traffic accidents (73.4%). The common clinical symptoms were malocclusion (96.7%) with occlusal interferences on posterior teeth and limited mouth opening (83.3%). On CT Scan, condylar neck fractures were the most common position (58.8%). There was a relationship between the side of deviated mouth opening and the affected sides (p < 0.05). In cases of unilateral condyle fractures, there was a relation between the side of premature contact on posterior teeth and the affected sides (p < 0.05). Conclusions: Fractures of condylar neck was the most common fractures in the mandibular condyle, which resulted in malocclusion, interferences on posterior teeth, limited and deviated mouth opening. There was a relationship between deviated mouth opening and premature contacts on posterior teeth with the fractured side.